Consumers’ choice model: an alternative meta-goals model focused on cognitive effort, justification, and regret - Park, Jisook "April" (Kansas State University, 2011)
Consumers’ choice behaviors are influenced by multifaceted decision factors. Information processing theory (Bettman, 1979) predicts that consumers’ decision processes are constructed at the time of a decision, and consumers’ meta-goals model (Bettman, Luce, & Payne, 1998) posits that their choice behaviors are generally guided by the minimization of cognitive effort and negative emotion, and the maximization of accuracy and justification. Insightful as this model may be at describing how consumers’ choices are shaped, it does not specify the interactions among the goals, assess the benefits of cognitive effort, or fairly evaluates the importance of emotion and justification in consumer decision making. Thus, the current studies collectively propose an alternative meta-goals choice model. Particularly, the current studies speculate on the importance of regret in consumer decision making. Consistent with previous research, Study 1 shows that participants trade-off between cognitive effort and accuracy goals depending on the monetary value of the products at hand, suggesting that the cognitive effort-accuracy trade-off may be moderated by price. Study 2 investigated the impact of cognitive effort on the experience of regret, showing the effectiveness of cognitive effort in attenuating the experienced regret. This relationship is explored with respect to the role of cognitive effort as a means of the justification factor in Study 3. Results showed that unjustified (wasted) cognitive effort did not make a substantial difference in post-purchase regret, but under spent cognitive effort generated more post-purchase regret. Study 4 examined both anticipated and experienced regret in relation to cognitive effort and justification; results showed that an exertion of cognitive effort is helpful in reducing the experience of regret but the justification of the choice also affects this relationship especially when the choice during the decision search is incongruent with the final decision. These results from current studies suggest interrelations between consumers’ four meta-goals. Based on these findings, an alternative meta-goals model is proposed which includes the benefits of cognitive effort exertion on consumer decision making, shedding light on how and when consumers choose to exert effort in an attempt to alleviate the potential future experience of regret.
Keywords: Consumer; Decision; Regret; Cognitive effort; Cognitive Psychology (0633); Psychology (0621)